2020
DOI: 10.5829/ije.2020.33.04a.06
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hand Skeletal Postures by Using Deep Convolutional Neural Networks

Abstract: Hand posture estimation attracts researchers because of its many applications. Hand posture recognition systems simulate the hand postures by using mathematical algorithms. Convolutional neural networks have provided the best results in the hand posture recognition so far. In this paper, we propose a new method to estimate the hand skeletal posture by using deep convolutional neural networks. To simplify the proposed method and to be more functional, the depth factor is ignored. So only the simple color images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Deep learning is a new machine learning approach in which high-level features are extracted from input data using hierarchical layers [14]. Deep learning has demonstrated excellent data processing performance by achieving excellent accuracy in image [15][16][17][18], video [19], natural language processing [20], time series [21] and audio processing [22]. Convolutional Neural Networks (CNNs) are among the deep learning algorithms that are suitable for image processing [23,24].…”
Section: Deep Learningmentioning
confidence: 99%
“…Deep learning is a new machine learning approach in which high-level features are extracted from input data using hierarchical layers [14]. Deep learning has demonstrated excellent data processing performance by achieving excellent accuracy in image [15][16][17][18], video [19], natural language processing [20], time series [21] and audio processing [22]. Convolutional Neural Networks (CNNs) are among the deep learning algorithms that are suitable for image processing [23,24].…”
Section: Deep Learningmentioning
confidence: 99%
“…The section presents a review of previous methods for predicting heart attacks. Gheitasi et al [3] used the C-Means fuzzy clustering method to predict heart disease. The study evaluated the proposed method with 270 samples and found that it was more accurate than the K-Means clustering method, with an accuracy of 92% .…”
Section: Related Workmentioning
confidence: 99%
“…The increasing demand for accurate and timely radiology reports, coupled with the challenges radiologists face in examining medical images and creating diagnostic notes, has led to burnout, errors, and delays in providing care [11]. While experts have turned to artificial intelligence and deep learning (DL) technologies to automate the generation of radiology reports, implementing and adopting these technologies, face several challenges [12,13]. These include the need to address concerns regarding the accuracy and reliability of automated notes, integrating these technologies into existing clinical workflows, and ensuring that they are accessible and affordable to all healthcare facilities.…”
Section: Problem Statement and Contributionmentioning
confidence: 99%